Dementia services for people from Black, Asian and Minority Ethnic and White‐British communities: Does a primary care based model contribute to equality in service provision?. (21st September 2020) - Dodd, Emily; Pracownik, Rebecca; Popel, Shaun; Collings, Stephen; Emmens, Tobit; Cheston, Richard
Abstract: This study set out to investigate whether there were disparities in service provision for people from Black, Asian and Minority Ethnic (BAME) communities compared to White British (WB) communities within a primary care led dementia service in the UK. Data were extracted from 30 cases from three BAME (African‐Caribbean, South Asian and Chinese) communities who had been referred to a dementia service between April 2016 and December 2017. We then extracted data from 30 WB cases matched for gender, age (within 5 years) and General Practitioner surgery. We compared service provision for both samples around assessment, diagnosis and post‐diagnostic support. The primary source of information in the BAME sample was less likely to be recorded as being the main carer and more likely to be an adult child. Cases from both samples were equally likely to have a CT scan. People from BAME communities were less likely to receive a cognitive assessment, and when they did they scored at a lower level. There was no difference between samples for the diagnoses that cases received, but BAME cases were more likely to be assessed as being low rather than medium or high risk. While cases from both samples were equally likely to receive medication, BAME cases were more likely to be seen by a psychiatrist. Significantly more people from the WB sample were recorded as using or being offered more than one form of community support. This study of a primary care‐based dementia service suggests that while many areas of service provision showed no evidence of inequality, important differences remain including the time at which people present for assessment and the range of post‐diagnostic services which are discussed. Further research is required to establish the likely causes of these disparities.